DAA1723 Fluid Mechanics Module - Nor Azlina, Alias (Penerbit Universiti Malaysia Pahang, 2016)
“To introduce the fundamental principles of fluid mechanics,the basic equations governing fluid statics and fluid flow, and the methods of solving engineering problems related to fluid mechanics”